Training Needs of Agricultural Axtension Workers in Al Balqa Governorate - Al-shadiadeh, Ahmad Nouri (Jordan Journal of Agricultural Sciences, 2021)
This study aimed to determine the training needs of agricultural extension agents in Al Balqa governorate /Jordan. The data were collected by using the rapid research method like a focus group. The group consisted of thirteen agricultural extension agents and agricultural engineers participating in extension tasks in the agricultural directorates and centers in the governorate that included (Kasbah of Salt, Ain Al-Basha, Al Fuhais, and Mahes, and agricultural centers in Al Subaihi and Allan). The respondents were asked about their training needs and determining their priorities by giving the training need’ a degree that ranged from (1-5) degrees according to of criteria for which relative weights were specified by participants group. The findings indicated that the training needs included seventeen subject matters, where rural leadership in agricultural extension, geographic information systems, and organic agriculture came in the first rank, communication skills, and integrated management of fruit trees in the second rank , livestock diseases in the third rank, then farms management of animal production in the fourth rank, irrigation and fertilization in the fifth rank, plant propagation and tissue culture in the sixth rank, plant protection in the seventh rank, varieties of fruit trees and vegetables in the eight rank, hydroponics in the ninth rank, ornamental plants in the tenth rank, the field schools in the eleventh rank, agricultural marketing and post-harvest techniques in the twelfth rank, agricultural projects management in the thirteenth rank, and food processing in the fourteenth rank, where the weighted degrees of these Needs (85,85, 85, 80, 80, 72.5, 66.67, 65.83, 43.33,42.5, 30.83, 27.5, 20, 15, 13.33, 11.67, 5.83) respectively. Finally, the result of this study recommended that the extension must take the extra role for Planning training programs for workers through preparing scientific and practical plans including training of extension agents in this study area.